Pengaruh Ekstrak Etanol Biji Jinten Hitam (Nigella Sativa) terhadap Ekspresi ET-1 Aorta pada Mencit Model Preeklampsia - Rubiati Hipni (Medical Laboratory Technology Journal, 2016)
Abstract: The objective of this research is to analyze the effects of ethanol extract of black cumin seeds (Nigella Sativa) to the expression of ET-1 Aorta given to the preeclampsia model mouse. The research design utilizes experimental and the kind of design used is posttest only control group design. Mice preeclampsia model. This research is divided into 6 groups, namely: Negative control, Positive control, Model + extract of black cumin seeds 500 mg/KgBB/day, 1000 mg/KgBB/day, 1500 mg/KgBB/day, and 2000 mg/KgBB/day. After conducting the surgery to the mouse, an examination is done to the expression of ET-1 Aorta by using Immunohistochemistry method. one way anova Were used as statistical analysis. There was an effect of treatment of giving the ethanol extract black cumin seeds of ET-1 Aorta to the preeclampsia model mouse (p